f(x)=f'(1)e^(x-1)-f(0)x+1/2 x^2,求f'(x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 09:06:13
f(x)=f''(1)e^(x-1)-f(0)x+1/2x^2,求f''(x)f(x)=f''(1)e^(x-1)-f(0)x+1/2x^2,求f''(x)f(x)=f''(1)e^(x-1)-f(0)x+1/
f(x)=f'(1)e^(x-1)-f(0)x+1/2 x^2,求f'(x)
f(x)=f'(1)e^(x-1)-f(0)x+1/2 x^2,求f'(x)
f(x)=f'(1)e^(x-1)-f(0)x+1/2 x^2,求f'(x)
令x=0,得f(0)=f'(1)/e
对原式两边求导得f'(x)=f'(1)e^(x-1)-f(0)+x,令x=1并把f(0)=f'(1)/e带入得f'(1)=f'(1)-f'(1)/e+1
则f'(1)=e,f(0)=1,带入f'(x)=f'(1)e^(x-1)-f(0)+x得f'(x)=e^x-1+x
f(e^x)=x,则f(1)*f(e)+f(e^2)等于多少?
f(2x+1)=e^x,求f(x)
f(x)=lnx+∫(1,e)f(x)dx-f '(1) ,求f(x)
f(x)=lnx+∫(1,e)f(x)dx-f '(1) ,求f(x)
有一个函数f(x),f(x)=f'(x),f(0)=1,证明:f(x)=e^x
设f(x)满足f(x)+f'(x)+f(x)=e^x+2,且f(0)=1,f'(0)=0,求f(x)
f(2x+1)=e^x,求f'(lnx)
设f(x)=e的y次方,证明:(1),f(x)f(y)=f(x+y) ,(2),f (x)/f(y)=f(x-y)
设f(e^x+1)=2lnx+x+1,求f(x),f(2x)
f(1+x)-2f(1-x)=3e^x求f(x)
F'(x)=f(x), F(0)=1, f(x)F(x)=x^2+e^x, 求f(x)
f(x)-f(1-x)=e^x怎样求f(x)
若f(x)=e^x+2∫(0 1)f(x)dx 求f(x)
f(x)=f'(1)e^(x-1)-f(0)x+1/2 x^2,求f'(x)
若f(x)=e^x/1+e^x+x∫f(x)dx 求f(x)=
2f(1+x)+f(1-x)=3e^x 求f‘(1)
已知f'(e^x)=xe^-x且f(1)=0 求f(x)
已知f'(e^x)=xe^(-x)且f(1)=0,求f(x)